Paving the road for a European postgraduate training curriculum. (August 2016) - van der Aa, Jessica E.; Goverde, Angelique J.; Teunissen, Pim W.; Scheele, Fedde
Abstract: The 'Project for Achieving Consensus in Training' has been initiated by the European Board & College of Obstetrics and Gynaecology to harmonise training in Obstetrics and Gynaecology throughout Europe. In this project called the EBCOG-PACT, a state of the art pan-European training curriculum will be developed. Implementation of a pan-European curriculum will enhance harmonisation of both quality standards of women's healthcare practice and standards of postgraduate training. Secondly, it will assure equal quality of training of gynaecologists, promoting mobility throughout Europe. Thirdly, it will enhance cooperation and exchange of best practices between medical specialists and hospitals within Europe. The project is expecting to deliver (1) a description of the core and electives of the curriculum based on previously defined standards of care, (2) a societally responsive competency framework based on input from societal stakeholders and (3) strategies for education and assessment based on the current literature. Also, the project focuses on implementation and sustainability of the curriculum by delivering (4) a SWOT-analysis for the implementation based on insights into transcultural differences, (5) recommendations for implementation, change management and sustainability based on the SWOT analysis (6) and finally a handbook for other specialties initiating European curriculum development. The development and the implementation of this modern pan-European curriculum in Obstetrics and Gynaecology aims to serve as an example for the harmonisation of postgraduate training in Europe.